A picture from thousands of words - Oishee, Kundu (Cranfield University, 2020)
The UK government announced its intention to purchase aircraft carriers in July 1998 and in December 2017 the first of the two ships were delivered to the Royal Navy. Newspaper reports on the procurement of the Queen Elizabeth class aircraft carriers have varied in their sentiment over the two decades- sometimes expressing positive, congratulatory emotions of pride and joy and at other times expressing criticism, anger, and despair at project management and outcomes. The image is a normalized plot of sentiment scores associated with 2,688 articles published in eleven British newspapers (broadsheets and tabloids) between 1998 and 2018, where sentiment scores have been calculated using the sentimentr package in R. This research method allows viewing project history at a glance, identifying and investigating critical periods of success and failure, accounting for wider public opinion towards public projects, and extracting greater meaning from textual data with speed and consistency.
Keywords: 'Sentiment analysis'; 'Megaprojects'; 'Aircraft carrier'; 'DSDS19'; 'DSDS19 Digital Image'; 'Business and Management not elsewhere classified'